08 Disruption of hexokinase II-mitochondrial binding affects cardiac oxygen consumption and lactate production in the beating heart. Issue 24 (24th November 2011) - Nederlof, R; Gürel, E; Koeman, A; Hollmann, M W; Southworth, R; Zuurbier, C J
Abstract : Background: The glycolytic enzyme hexokinase (HK) is located either in the cytosol or bound to mitochondria (mitoHK). We recently demonstrated that a decrease in mitoHK increased cardiac ischaemia (I)-reperfusion (R) injury and cardiac remodelling, and prevented ischaemic preconditioning. However, the physiological implication of HK binding to mitochondria is unknown. Hypothesis: In the present study we hypothesise that mitoHK affects cardiac oxygen consumption (MVO2) and glycolysis-glucose oxidation coupling (lactate efflux). Methods and Results: Isolated Langendorff perfused rat hearts (substrate 10 mM glucose) were treated 20 min with saline (control group 1), 1 μM TAT only (control group 2), 200 nM TAT-HKII or 1 μM TAT- HKII, followed by 15 min I and 30 min R. TAT-HKII peptide contains the binding motif of HKII with mitochondria and was shown to displace HKII from mitochondria. MVO2 and lactate efflux were measured during peptide treatment. Low-dose TAT-HK reduced cardiac MVO2 by approximately 10%. High-dose TAT-HK only transiently reduced MVO2, with increased MVO2 at the end of peptide treatment. Effluent lactate concentration increased dose-dependently with TAT-HK peptide treatment from 0.02 to 0.03 mM (control groups) to 0.06 mM (200 nM TAT-HK) and 0.09 mM (1 μM TAT-HK). No cell necrosis was observed in both control groups following IR. However, TAT-HK treatment dose-dependently increased cell necrosis. Peptide treatment was not associated with changes in MDA or aconitase activity. Conclusions: This study shows for the first time that mitoHK affects cardiac MVO2. In addition, our data suggest that mitoHK may also determine glycolysis-glucose oxidation coupling.